Optimization of culture conditions for gamma-aminobutyric acid production by newly identified Pediococcus pentosaceus MN12 isolated from âmam nemâ, a fermented fish sauce - Thuy, D.T.B. (Bellwether Publishing, Ltd., 2021)
This study was aimed to identify and optimize the culture conditions for gamma-aminobutyric acid (GABA) production by a lactic acid bacterium strain isolated from mam nem, a fermented fish sauce. Among the six isolates obtained from mam nem, the MN12 had the most potent GABA-producing capability. The strain was then identified to be Pedioccocus pentosaceus by employing MALDI-TOF-MS and phenylalanyl-tRNA synthase sequencing methods. The initial cell density of 5.106 CFU/mL, monosodium glutamate concentration of 60Â mM, initial pH of 7, temperature of 45Â°C and cultivation time of 72Â h were found to be the optimal culture conditions for highest production of GABA, reaching 27.9Â Â±Â 0.42Â mM, by this strain. The cultivation conditions for GABA production by P. pentosaceus MN12 have been successfully optimized, providing a foundation for the development of fermented foods enriched with GABA. Â© 2020 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.